Ceratopteris thalictroides (L.) Brongn. (Pteridaceae): Confirmation of its presence in the pteridoflora of Peru - Freddy Peláez; Blanca León; Narda Alarcón (Acta Botânica Brasílica)
Abstract We report the presence of Ceratopteris thalictroides based on a recent collection from northeastern Peru. This aquatic fern is widely distributed in the tropics, however, its presence in Peru remained uncertain and without a voucher until now. This finding increases to four the number of species of the subfamily Parkerioideae, Pteridaceae within Peru.